KINERJA PRAMUGRAHA DALAM MEMBERSIHKAN KAMAR TAMU DI HOTEL X - Yasa, I Kadek Adi Dharma; Wulan, Anak Agung Istri Ratna Sari; Sunarsa, I Wayan (Journal of Hospitality Accommodation Management (JHAM), 2025)
This study aims to determine the performance of room attendants in cleaning guest rooms at The St. Regis Bali Resort Hotel. The theory used is the theory (Robins, 2016), which sets 4 indicators to assess employee performance: work quality, work quantity, responsibility, and cooperation. The research method used in this research is descriptive qualitative. The data collection methods used for observation, interviews, and documentation studies. Based on the results of the data analysis, 2 indicators still need improvement, and 2 indicators are good and need to be maintained. The results of the total performance of room attendants in cleaning guest rooms at The St. Regis Bali Resort show that 82% have been done and 18% have not. Suggestions that can be given are that the manager or supervisor always provides input, direction, and intensive training and is expected to increase the discipline of the room attendants so that the work results will be better in the future.